Interdisciplinaridade e modelagem matemática: saberes docentes em movimento na formação de professores - Borges, Maria Fátima Cursino (2007)
The present work consists of a carried through qualitative research with a group of pupils of the last period of the Course of Licenciatura in Mathematics of the Federal University of Uberlândia- MG- initiated in 2006 and concluded in the year of 2007. The citizens of the research were young with age between 21 and 25 years. The objective of the research was to investigate the possibilities to use Mathematical Modeling in the work to interdisciplinar, mainly between Biology and the Mathematics. The activities of the Research had been carried through with pupils of Disciplina of Workshop of Practical Pedagogical, in which the pupils present practical workshops, on subjects chosen for them. The subjects all would have to approach: History of the Mathematics, Analysis of sites, didactic book Analysis, Activities with Etnomatemática, Games and Mathematical Modeling. The production of data was given by means of answers of questionnaires, Interview, or Collective Colloquy with the students and comment of lessons for the researcher. These data had been analyzed respecting it research modality (qualitative) and also aiming at to take care of to the objectives considered for the research. We point the Mathematical Modeling as strategy with respect to the practical one of the Interdisciplinaridade during the Formation of the Future Professors of Mathematics as well as the consequences of this methodology in the professional development of the same ones.